’Us’ before the ’violent and criminals’. Guillermo Lasso’s speech during the 2022 national strike in Ecuado: ’Us’ before the ’violent and criminals’. Guillermo Lasso’s speech during the 2022 national strike in Ecuador - Andino Veloz, Byron (Quórum Académico, 2023)
The objective is to analyze the discursive strategies of the President of Ecuador, Guillermo Lasso, during the 2022 National Strike. It is a qualitative and interpretative study, based on political discourse (recipients and entities of the imaginary) and discursive ethos. The corpus has eight Lasso speeches on national channels. Among the results are: the construction of others as "violent" and "criminals", delegitimizes indigenous leaders and the mobilization as destabilizing, considers community protesters as subjects that can be manipulated; the ’we’ is made up of the institutional: the Government, the Police and the Armed Forces, with political and geographical articulations; also tries to persuade pararecipients. Lasso tried to build his ethos as competent, combative and dialoguing, with rationality